2012
DOI: 10.1136/vr.100147
|View full text |Cite
|
Sign up to set email alerts
|

Survey of veterinary surgeons on the introduction of serological testing to assess revaccination requirements

Abstract: Despite the discussion of the use of serological testing in canine vaccination protocols, no study has been published that investigates the opinions of the veterinary profession regarding the use of the test to assess revaccination requirements in dogs. This paper presents the results of a study designed to fill this research gap which was completed in 2009. Veterinary surgeons were asked to complete a questionnaire on different aspects of canine vaccination and the introduction of serological testing to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…(2004). During the 13‐year period since publication of that study, UK canine core vaccines have been licensed with a minimum DOI of 3 years, and a number of practice groups have begun to implement in‐practice serological testing to inform decision‐making about canine core revaccination (Heayns & Baugh 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2004). During the 13‐year period since publication of that study, UK canine core vaccines have been licensed with a minimum DOI of 3 years, and a number of practice groups have begun to implement in‐practice serological testing to inform decision‐making about canine core revaccination (Heayns & Baugh 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Protective antibody concentrations against CDV, CAV and CPV2 were present in 71·5%, 82% and 95% of the population, respectively. Given the changes in advice regarding core revaccination and serological testing since that time (Heayns & Baugh 2012), and the more recent availability of in‐practice test kits, the aim of the present study was to use such a kit to determine current levels of seroprotection in a sample of the UK dog population.…”
Section: Introductionmentioning
confidence: 99%
“…The overall response rate for the survey was 50%, considered satisfactory when compared to previously published veterinary questionnaires (Dyson et al 1998;Wagner & Hellyer 2000;Bland et al 2009;Verwilghen et al 2011;Heayns & Baugh 2012). Wagner reported a response rate of 32% (Wagner & Hellyer 2000), and Bland about 40% (Bland et al 2009).…”
Section: Discussionmentioning
confidence: 69%
“…; Verwilghen et al. ; Heayns & Baugh ). Wagner reported a response rate of 32% (Wagner & Hellyer ), and Bland about 40% (Bland et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although these tests are commonly used for the diagnosis of disease, a study by Heayns and Baugh (2012) found that 69.5 per cent of veterinary surgeons would consider using serology to tailor vaccination protocols in dogs 13,16 …”
Section: Assessing Humoral Immunity In Practicementioning
confidence: 99%